Curcumin inhibits bladder cancer progression via regulation of β-catenin expression - Jing Shi; Yunpeng Wang; Zhuomin Jia; Yu Gao; Chaofei Zhao; Yuanxin Yao (Tumor Biology)
Bladder cancer has a considerable morbidity and mortality impact with particularly poor prognosis. Curcumin has been recently noticed as a polyphenolic compound separated from turmeric to regulate tumor progression. However, the precise molecular mechanism by which curcumin inhibits the invasion and metastasis of bladder cancer cells is not fully elucidated. In this study, we investigate the effect of curcumin on the bladder cancer as well as possible mechanisms of curcumin. The expression of β-catenin was detected by quantitative real-time polymerase chain reaction and immunohistochemical analysis in a series of bladder cancer tissues. In addition, bladder cancer cell lines T24 and 5637 cells were treated with different concentrations of curcumin. The cytotoxic effect of curcumin on cell proliferation of T24 and 5637 cells was measured by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. The migration and invasion capacity of T24 and 5637 cells were measured by transwell assay. The effects of curcumin on expression levels of β-catenin and epithelial–mesenchymal transition marker were determined by western blotting. The β-catenin expression was significantly upregulated in bladder cancer tissues when compared with corresponding peri-tumor tissues. Furthermore, curcumin inhibited the cell proliferation of T24 and 5637 cells, and curcumin reduced the migration and invasive ability of T24 and 5637 cells via regulating β-catenin expression and reversing epithelial–mesenchymal transition. Curcumin may be a new drug for bladder cancer.